Concepts for chemical state analysis at constant probing depth by lab‐based XPS/HAXPES combining soft and hard X‐ray sources. (27th April 2020) - Siol, Sebastian; Mann, Jennifer; Newman, John; Miyayama, Takuya; Watanabe, Katsumi; Schmutz, Patrik; Cancellieri, Claudia; Jeurgens, Lars P.H.
Abstract : The greater information depth provided in hard X‐ray photoelectron spectroscopy (HAXPES) enables nondestructive analyses of the chemistry and electronic structure of buried interfaces. Moreover, for industrially relevant elements like Al, Si, and Ti, the combined access to the Al 1s, Si 1s, or Ti 1s photoelectron line and its associated Al KLL, Si KLL, or Ti KLL Auger transition, as required for local chemical state analysis on the basis of the Auger parameter, is only possible with hard X‐rays. Until now, such photoemission studies were only possible at synchrotron facilities. Recently, however, the first commercial XPS/HAXPES systems, equipped with both soft and hard X‐ray sources, have entered the market, providing unique opportunities for monitoring the local chemical state of all constituent ions in functional oxides at different probing depths, in a routine laboratory environment. Bulk‐sensitive shallow core levels can be excited using either the hard or soft X‐ray source, whereas more surface‐sensitive deep core‐level photoelectron lines and associated Auger transitions can be measured using the hard X‐ray source. As demonstrated for thin Al2 O3, SiO2, and TiO2 films, the local chemical state of the constituting ions in the oxide may even be probed at near‐constant probing depth by careful selection of sets of photoelectron and Auger lines, as excited with the combined soft and hard X‐ray sources. We highlight the potential of lab‐based HAXPES for the research on functional oxides and also discuss relevant technical details regarding the calibration of the kinetic binding energy scale.